Indole acetic acid (IAA) product Indole acetic acid (IAA) production by endophytic bacteria from Stem And Roots Of Indian Ash Tree (Lannea Coromandelica): Indian Ash Tree (Lannea Coromandelica) - Hala, Yusminah; Ali, Alimuddin; Suryani, A. Irma (Jurusan Biologi Universitas Negeri Makassar, 2024)
The endophytic bacteria live in healthy plants and can even improve plant health and productivity by suppressing pathogenic bacteria and increasing plant growth due to the producing IAA hormone. The purpose of this study was to describe the ability of each bacterial isolate to produce IAA hormone, to determine the fluctuations that occur during the five-day incubation period. The endophytic bacterial isolates from the roots of the Indian ash tree are A1 Bacillus, A2 Bacillus, A3 Bacillus, A4 Pseudomonas and A5 Bacillus, while from the stems are B1 Bacillus, B2 Agrobacterium, B3 Bacillus, B4 Bacillus and B5 Agrobacterium. The potential of bacterial isolates in producing IAA hormone was obtained by measuring the absorbance value using a spectrophotometer at a wavelength of 530 nm which was carried out every day for five days of incubation. The results obtained showed that endophytic bacterial isolates from the roots and stems of Kayu Jawa Plants have the ability to produce IAA with the highest concentration on 3 days of incubation was produced by isolate A3 (7.95 ppm), from the genus Bacillus, on 4 days of incubation the highest concentration was produced by A2 (22.18 ppm) from the genus Bacillus and on 5 days of incubation the highest concentration was produced by A2 (57.60 ppm) from the genus Bacillus.